From a religious view of madness to religious mania: the Encyclopédie, Pinel, Esquirol. Issue 2 (June 2017) - Huneman, Philippe
This paper focuses on the shift from a concept of insanity understood in terms of religion to another (as entertained by early psychiatry, especially in France) according to which it is believed that forms of madness tinged by religion are difficult to cure. The traditional religious view of madness, as exemplified by Pascal (inter alia), is first illustrated by entries from the Encyclopédie . Then the shift towards a medical view of madness, inspired by Vitalistic physiology, is mapped by entries taken from the same publication. Firmed up by Pinel, this shift caused the abandonment of the religious view. Esquirol considered religious mania to be a vestige from the past, but he also believed that mental conditions carrying a religious component were difficult to cure.